Possibilities for correcting diffuse alopecia associated with prior coronavirus infection (COVID-19) - Natalia V. Shperling; Maksim I. Shperling; Irina I. Gnatiuk (ZAO "Consilium Medicum", 2021)
Diffuse alopecia (DA) is a disease characterized by a diffuse hair loss associated with alterations in physiological hair cycle due to an exposure of hair follicles to various endogenous and exogenous factors. The disease is mainly caused by alterations in the cyclicity of hair follicle phases anagen, telogen and catagen. Pathogenetic therapy for DA is based on the initiation and lengthening of the anagen phase, in particular, via inhibition of catagen. Given a high prevalence of DA following a new coronavirus infection (COVID-19), the search for an effective medicine for the SARS-CoV-2 virus-associated DA is extremely important. The use of drugs derived from natural products can have a beneficial effect on the disease following COVID-19. The study was aimed to assess the efficacy of the combination of Selencin (homeopathic drug) and Selencin Peptide Active (peptide lotion) for the treatment of DA associated with prior coronavirus infection (COVID-19). A total of 34 patients with a confirmed diagnosis of telogen/anagen DA, who noted the relationship between DA and a new coronavirus infection, were treated with both systemic (pills) and topical (peptide lotion) Selencin for 2 months. The study showed a high efficacy of the treatment, i.e., a significant reduction in hair loss, as well as restoration of their structure and increase in volume. Also, after 2 and 4 months of treatment, there was a normalization of dermatoscopic picture of the scalp and an improvement in the special tests (PULL test). Thus, the use of the combined drug Selencin for SARS-CoV-2 virus-associated DA has a pronounced therapeutic effect. The drug can be used as the main treatment for this disease if it associated with COVID-19.